Development and validation of questionnaire to assess preschool teachers’ knowledge, attitude, and self-efficacy on performing first-aid in children - Prasetya, Damar; Salim, Rose Mini Agoes (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Despite the importance of performing first aid in child emergencies and injuries, a tool that assess preschool teachers’ knowledge, attitude, and self-efficacy in performing these particular skill is still lacking. This study aims to validate the content and face validity of this questionnaire about performing first aid in specific preschool teacher population based on American Heart Association (AHA) recommendation. Content and face validation index were measured in this study. The questionnaire, initially comprising 40 items across three domains (knowledge, attitude, and self-efficacy), was derived from extensive literature review, guidelines, and expert suggestions. Evaluation was performed by eight experts and initial testing conducted on preschool teachers which resulted in a final version with 34 items —18 for knowledge, 4 for attitude, and 12 for self-efficacy—demonstrating strong content and face validity. This questionnaire is then considered valid to be tested in the subsequent phase reliability study and can contribute to assess and to improve preschool teachers’ competence in performing first aid for children.